Choco Fruity / Fairus Izyan Ahmad ... [et al.] - Ahmad, Fairus Izyan; Mah-Mhad Zul Kenedy, Nur Faiqah; Mat Tamizi, Nurainin Sofiya; Hasni, Arifah Amirah; Zulkarnain, Athirah' (2021)
We are starting a business of manufacturing chocolate jars. The name of this company is Choco Fruity. Choco Fruity offers choco jars products that are more likely to meet customer needs. This is because innovation allows the business to be updated with the latest changes in tastes and preferences of the consumers and hence, to serve those preferences and increase its profits. The uniqueness of this product is the ingredients that we used in the choco jar. We used the quality chocolate which is Beryl’s to melt it together with the quality of bubble rice to maintain its crispiness. We have three types of chocolate which are dark chocolate, milk chocolate and white chocolate. It also comes with a variety of toppings which most of them are well-known fruit such as dates, fresh strawberry, kiwi and blueberry. We have ‘signature ‘topping which is fresh fruit and it is classified under ‘signature’ because it is different compared to other choco jar businesses. The most important thing is our choco jar is 50% less sweet. Choco Fruity’s customers are obviously from chocolate lovers who are diabetics, old people and who like to eat less sweets. It is also suitable to be given as a gift to someone. In Putrajaya, there are few competitors such as Choco Crispy, Choco Tub, Chocojarlicious and others. However, Choco Fruity is beneficial to be compared to other competitors because the toppings are different from others with affordable prices. It also has the ‘signature’ fresh fruit topping. Besides that, it is less sweet while they are not. The management of Choco Fruity consists of the presidents who will lead the company, a financial manager, a production manager, a promotional manager and one who handles customer care. We also created facebook to expand our business through social media and learn how to post facebook posts for business products. Furthermore, to make it easier, we signed up for the eUsahawan portal to track our business for profits and revenues. For now, we have a product and service commitment plan to promote the product. We can do both postage and delivery for customers. However, they still have the selected area for delivery.